RISK FACTORS AND FEATURES OF THE COURSE OF CANDIDA PNEUMONIA IN CHILDREN - Nabieva Zumrat Tukhtaevna (Western European Studies, 2024)
In the last decade mycoses have become a serious clinical problem for neonatal intensive care units. To date, fungal infections confidently occupy the 3rd place among hospital infections. This is due to the constant improvement of modern technologies for providing intensive care to premature infants and with a significant increase in survival among this category, there is a need to use various invasive methods of treatment, such as artificial lung ventilation (ventilator), long-term parenteral nutrition, prolonged catheterization of central veins, which contribute to fungal colonization and the formation of biofilms as a reservoir for systemic spread of fungi.
Keywords: contribute; mycoses; premature